Susceptibility to short-term ozone exposure and cardiovascular and respiratory mortality by previous hospitalizations - Auriba Raza; Marcus Dahlquist; Tomas Lind; Petter L. S. Ljungman (BMC, 2018)
Abstract Background Ozone (O3) has been associated with cardiorespiratory mortality although few studies have explored susceptible populations based on prior disease. We aimed to investigate the role of previous hospitalization on the association between short-term exposure to O3 and cardiovascular (CV) and respiratory mortality. Methods We performed time series analyses using generalized additive models and case-crossover on 136,624 CV and 23,281 respiratory deaths in Stockholm County (1990-2010). Deaths were linked to hospital admissions data. We constructed 2-day and 7-day averages using daily 8-h maximum for O3 and hourly values for PM2.5, PM10, NO2, and NOx from a fixed monitor. Results We observed a 0.7% (95% CI: 0.1%, 1.3%) and 2.7% (95% CI: 0.8%, 4.6%) higher risk of CV and respiratory death per 10 μg/m3 higher 2-day and 7-day average O3 respectively. Individuals previously hospitalized for myocardial infarction demonstrated 1.8% (95% CI: 0.4%, 3.4%) higher risk of CV death per 10 μg/m3 higher 2-day average O3 and similar associations were observed in individuals with no previous hospitalization for any cause. Individuals with previous hospitalizations did not show susceptibility towards O3-related risk of respiratory mortality. We observed no associations for other pollutants. Conclusion Short-term ozone exposure is associated with CV and respiratory mortality and our results may suggest higher susceptibility to CV mortality following O3 exposure in individuals previously hospitalized for myocardial infarction. Higher risks were also observed in individuals with cardiovascular death as their first presentation of disease.